Use of Cognitive Interviews in the Development of a Survey Assessing American Indian and Alaska Native Adult Perspectives on Genetics and Biological Specimens - Hiratsuka, Vanessa Y.; Beans, Julie A.; Byars, Christie; Yracheta, Joseph; Spicer, Paul G. (International journal of environmental research and public health, 2024)
The cognitive interview process is a method to validate a survey instrument’s face validity and enhance confidence in item interpretation, as well as a method to engage communities in the research process. Trained American Indian and Alaska Native (AIAN) interviewers conducted retrospective cognitive interviews at three AIAN communities to assess the item quality of a 131-item survey item that measures AIAN knowledge and attitudes on genetics and biological specimens. A cognitive interview process was used to assess cultural consonance, thought processes used when considering survey instructions, items and responses, and language preference of survey items in the development of a survey to assess public knowledge and attitudes on genetics. Content analysis was used to analyze interview data. Survey instructions, items and scales generated no cognitive difficulties. The participants noted being unfamiliar with terminology used to describe genetic and biological specimens. In several cases, the participants’ written response in the survey and verbal response in the interview did not align. A resultant 52-item survey for use in AIAN communities was finalized. Cognitive interviewing is resource-intensive; however, ignoring community engagement during survey development results in inappropriate interpretations about culturally diverse populations such as AIAN peoples.